Pancasila Laboratory between Practical Urgency and the Absence of Standardization within the Formal Education Environment - Ruhadi Ruhadi; Hafiz Rafi Uddin; Novia Wahyu Wardhani; Munadi Munadi (Universitas Negeri Semarang, 2026)
The Pancasila Laboratory is a strategic instrument in strengthening Pancasila values education through contextual, reflective, and experience-based learning for young citizens. Although its urgency is recognized, to date, there has been no standardization of conceptual, operational, or evaluative standards, even though its development is based on ideology. Standardization is needed not to impose uniform practices, but to provide a flexible, context-specific minimum quality framework that guarantees the function, process, and achievement of values. This study uses a qualitative, multi-case study design and a conceptual analysis of the Character Padepokan at UNNES, the Bhinneka Tunggal Ika Laboratory at SMK Negeri 1 Sambi, and the Pancasila Laboratory School by YPLP. Data were collected through in-depth interviews, participatory observation, and documentation. The results of the study show that there is no uniform national model, but laboratory practices have developed organically through an approach of experience, reflection, collective participation, and the formation of values through habit. The findings emphasize the need for a flexible and adaptive standardization framework to ensure consistency in quality and measurable outcomes. The integrated conceptual model offered has the potential to strengthen character education, civic engagement, and the sustainability of Pancasila ideology within the national education system.